Current Cigarette Smoking Is Associated With a High Seizure Frequency and Anxiety Symptoms in People With Epilepsy - Zhong, Rui; Li, Zhuan; Zhang, Xinyue; Chen, Qingling; Lin, Weihong (Frontiers in Neurology, 2022)
Abstract Purpose: This study aimed to answer the following questions: How many people with epilepsy (PWE) have cigarette smoking habits? Which demographic or clinical characteristics are associated with cigarette smoking? Is cigarette smoking related to depressive and anxiety symptoms in persons with epilepsy? Methods: A total of 524 PWE were included in the final analysis. Demographic and clinical data were gathered and recorded. Smoking status was identified. The associations of smoking status with the clinical features of epilepsy and depressive and anxiety symptoms were evaluated by logistic regression models. Results: The overall prevalence of cigarette smoking was 23.5% (123 PWE) in this sample. In the multivariate logistic regression model, male sex (adjusted OR=10.414, 95% CI: 5.552-19.535, P＜0.001), high seizure frequency (adjusted OR=1.474, 95% CI: 1.043-2.084, P=0.028), and anxiety symptoms (adjusted OR=2.473, 95% CI: 1.483-4.112, P=0.001) were shown to have independent associations with cigarette smoking in PWE. Conclusion: Our findings suggested that the overall prevalence of cigarette smoking was 23.5% in adults with epilepsy, which is slightly lower than that (26.6%) in general adults in China. In the present study, cigarette smoking was associated with male sex, high seizure frequency and anxiety symptoms in PWE. Further prospective clinical studies with larger sample sizes are required to confirm our findings.